2023
DOI: 10.1186/s13046-023-02860-5
|View full text |Cite
|
Sign up to set email alerts
|

FAM171B stabilizes vimentin and enhances CCL2-mediated TAM infiltration to promote bladder cancer progression

Wei-Min Hu,
Ming Li,
Jin-Zhuo Ning
et al.

Abstract: Background Invasion and metastasis are the main causes of unfavourable prognosis in patients diagnosed with bladder cancer. The efficacy of immunotherapy in bladder cancer remains suboptimal due to the presence of an immunosuppressive microenvironment. The novel protein family with sequence similarity 171B (FAM171B) has been identified, but its precise role and mechanism in bladder cancer remain unclear. Methods In this study, we conducted an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…As an intermediate filament protein, vimentin is primarily expressed in mesenchymal cells, regulating cell shape, adhesion, and migration through its interactions with other proteins and its role in maintaining cytoskeletal structure, under physiological conditions [ 33 , 34 , 48 50 ]. Nevertheless, as we shown in LUAD cells in this study, vimentin expression is often upregulated in cancer cells, in particular, in those that have undergone the EMT [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an intermediate filament protein, vimentin is primarily expressed in mesenchymal cells, regulating cell shape, adhesion, and migration through its interactions with other proteins and its role in maintaining cytoskeletal structure, under physiological conditions [ 33 , 34 , 48 50 ]. Nevertheless, as we shown in LUAD cells in this study, vimentin expression is often upregulated in cancer cells, in particular, in those that have undergone the EMT [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al ( 74 ) found that SAF-A also binds to P-element-induced wimpy testis-interacting RNA-1742 (piRNA-1742) to stabilize USP8 mRNA and promote the progression of renal cell carcinoma. Through interaction with a family with sequence similarity 171 B (an independent prognostic factor for bladder cancer progression), SAF-A regulates the CCL2 pathway to facilitate M2 macrophage polarization in the tumor microenvironment, thereby promoting bladder cancer development ( 75 ).…”
Section: Clinical Significance Of Saf-amentioning
confidence: 99%
“…Compositions of chemokines within the TME substantially shape the direction and characteristics of macrophages. Specifically, chemokine (C-C motif) ligand 2 (CCL2) plays a crucial role in recruiting TAMs and contributes to bladder cancer cell proliferation, metastasis, and the establishment of an immunosuppressive environment in the TME [ 102 , 103 ]. Infiltrating TAMs can promote tumor development by altering the microenvironment of bladder cancer through the action of C-X-C motif chemokine ligand 8 (CXCL8) [ 103 ].…”
Section: Factors That Bladder Tumors Exploit To Avoid Immune Responsesmentioning
confidence: 99%
“…CCL2, a significant chemokine crucial for macrophages, exhibits high expression within cancer cells. It is actively secreted by these cells [ 102 ]. Several research studies have shown that CCL2 can promote the M2 polarization of TAMs, consequently amplifying immunosuppressive properties within the TME [ 180 , 181 ].…”
Section: Potential Therapeutic Strategies For Modulating Immune Evasionmentioning
confidence: 99%
See 1 more Smart Citation